Somanatha, the many voices of a history - Thapar, Romila (New Delhi ; New York, NY : Penguin, Viking, 2004)
History and sources of Somanatha Temple; a study.
Includes bibliographical references (p. [237]-250) and index.
Keywords: Mahmud, -- Sultan of Ghazni, -- 971-1030.; Somanatha Temple (India) -- History -- Sources; India -- History -- 1000-1526 -- Sources; India -- History -- 1000-1526 -- Historiography